C-Press Technique to Facilitate Descemet Membrane Endothelial Keratoplasty Surgery in Vitrectomized Patients: A Case Series. Issue 9 (September 2019) - Saad, Alain; Awwad, Shady T.; El Salloukh, Nasrine Anais; Panthier, Christophe; Bashur, Ziad; Gatinel, Damien
Abstract : Purpose: To describe an original technique to unfold the graft in vitrectomized eyes undergoing Descemet membrane endothelial keratoplasty (DMEK). Methods: We performed a retrospective chart and video review of successive cases presenting with corneal decompensation in vitrectomized eyes or aphakic eyes in which DMEK or combined DMEK/scleral-fixated intraocular lens implantation was indicated and in which a specific technique [Cornea-Press (C-Press)] was used to unfold the graft. C-Press is characterized by corneal indentation intended to artificially shallow the anterior chamber and allow the graft to unroll. Best spectacle-corrected visual acuity, central corneal thickness, the time of graft unfolding, endothelial cell count, and the incidence of intraoperative/postoperative complications were analyzed. Results: Eleven eyes of 11 patients (8 men, mean age: 73 ± 12 years) were included. Corrected distance visual acuity (logarithm of the minimum angle of resolution) improved from 1.44 ± 0.23 preoperatively to 0.77 ± 0.36 6 months postoperatively ( P < 0.001). Central corneal thickness (CCT) decreased from 644 ± 79 preoperatively to 516 ± 49 μm 6 months postoperatively. The graft unfolding time was 4.4 ± 2.5 minutes. Mean endothelial cell density was 2762 ± 192 preoperatively and 1872 ± 324 cells/mm 2 6 months postoperatively. No eye showed intraoperative complications. Rebubbling for partial detachment was needed in 2 cases (18%). Conclusions: The C-Press technique enables likely safe and reproducible DMEK surgery in vitrectomized eyes. Further clinical studies with a large number of patients and longer follow-up are required to confirm our preliminary results. Abstract : Supplemental Digital Content is Available in the Text.